Kepentingan Nasional Indonesia dalam Keanggotaan BRICS terhadap Ekonomi Nasional Tahun 2023-2024 - Salma Alfiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines Indonesia's national interests in BRICS membership for the national economy in 2023–2024. Indonesia has officially announced its readiness to join BRICS, which emphasizes the principles of free and active participation and a multipolar orientation in the global economy. This study aims to analyze how Indonesia's involvement in economic cooperation forums for developing countries such as BRICS can influence the direction of development and national economic interests, both in terms of opportunities and risks. This study uses a qualitative-descriptive approach using literature study and interviews. The theories used are Neoliberal Institutionalism, Regional Economic Integration, and National Interest as the basis for explaining Indonesia's involvement in international cooperation. The results show that Indonesia's membership in BRICS has the potential to expand access to development financing through the New Development Bank (NDB), strengthen trade and investment with BRICS member countries, and enhance leading sectors such as the manufacturing industry and agriculture, which have shown significant export increases, especially to BRICS member countries. However, there are risks that must be anticipated, such as the dominance of large countries in BRICS, the potential for new economic dependencies, and geopolitical friction with Western countries. BRICS membership can be an opportunity for Indonesia's national development if managed carefully, selectively, and with a focus on long-term interests.